Chronic cannabidiol treatment induces cardiovascular improvement in renovascular hypertensive rats - Flôr, Atalia Ferreira Lima; Duarte-Maia, Samuel; Fernandes-Costa, Francineide; Souza, Rayane Maria Pessoa De; Braga, Valdir De Andrade; Do Amaral, Sandra Lia [UNESP]; Mascarenhas, Sandra Rodrigues; Brito-Alves, José Luiz; Colombari, Debora Simoes Almeida [UNESP]; Cruz, Josiane Campos (Wolters Kluwer, 2024)
Background: Cannabidiol (CBD) is increasingly studied for its therapeutic potential in neurodegenerative diseases. Previous research on acute CBD administration has demonstrated cardiovascular benefits in hypertensive rats, including reduced mean blood pressure and oxidative stress. Aim: To investigate the long-term cardiovascular effects of chronic CBD treatment in renovascular hypertension induced by the 2-kidney-1-clip (2K1C) model. Methods: Male Wistar rats (180-200 g, 8 weeks old) underwent 2K1C or SHAM surgery. Six weeks later, rats received chronic CBD treatment (20 mg/kg, twice daily for 14 days). A combination of ex vivo, in vitro, and in vivo methods was used to assess CBD's cardiovascular effects in 2K1C hypertensive rats. Results: Chronic CBD treatment significantly reduced blood pressure and the depressor response to hexamethonium (a ganglionic blocker). It also normalized variability in low-frequency (LF) power and LF/high-frequency (HF) ratio. CBD enhanced vasodilation and reduced vasoconstriction in the mesenteric artery of 2K1C rats, accompanied by decreased expression of aortic reactive oxygen species (ROS). Conclusion: Our findings suggest that chronic CBD treatment exerts antihypertensive effects by improving baroreflex sensitivity and vascular function while decreasing arterial ROS levels and sympathetic nerve activity. These results underscore CBD's potential therapeutic role in managing cardiovascular complications associated with renovascular hypertension.
Keywords: baroreflex; cannabidiol; hypertension; reactive oxygen species; spectral analyses